Distance students' readiness for and interest in collaboration and social media. Issue 1 (2013) - ,; ,; ,; ,
Abstract : Purpose – The purpose of this paper is to describe how researchers from four large Canadian distance education or dual mode institutions conducted a survey aiming to describe the use of and interest in social software and Web 2.0 applications by distance education students and to measure their interest in collaborating with peers.Design/methodology/approach – In order to do this, an online questionnaire was distributed to students from four large Canadian distance education institutions. A systematic sampling procedure led to 3, 462 completed questionnaires. The results show that students have diverse views and experiences, but they also show strong and significant age and gender differences in a variety of measures, as well as an important institution effect for interest in collaboration.Findings – Males and younger students score higher on almost all indicators, including cooperative preferences. In this paper the authors review quantitative results from the survey from earlier work (Poellhuber et al. ) and present an analysis of the qualitative data gathered from open‐ended questions in the survey. Answers to open‐ended questions regarding the expectation and interest in using social software in their courses, show that students have positive expectations about interactions and course quality, but also concerns about technical, time, and efficiency issues.Research limitations/implications – The probabilist sampling, as well as the high number of respondents, are forces. The limits of the research are linked to its survey methodology, possible self‐selection bias, history effect and social desirability effect.Practical implications – The study opens avenues to those who consider the integration of social software or Web 2.0 tools in distance courses.Social implications – It also offers guidance to those who consider using social software for learning purposes in general.Originality/value – While social media and social networking tools offer new educational affordances and avenues for students to interact, that may alleviate the drop‐out rate problem faced by distance education institutions. Little is known about distance students' expertise with social media or their interest in using them to learn individually or to collaborate with peers.